Burnout Among ENT Residents During Covid-19 Pandemic: What Are The Contributing Factors? - Andrey Dwi Anandya; Abla Ghanie; Ahmad Hifni (Journal of Anesthesiology and Clinical Research, 2021)
Introduction. Resident doctors are susceptible to burnout syndrome, which are the combination of physical and psychological fatigue, that may affect their performance. Long-term pandemic of Covid-19 may also contribute to increase the severity of burnout among residents doctor, might be because the increasing of work time and effort to treat the patients during the time while maintaining prevention against the possible exposure that may harm themselves. This study was aimed to evaluate burnout prevalence among ENT (Ear-Nose-Throat) medical residents in Covid-19 pandemic, and its relation to certain factors of demographic and wellness. Methods. Thirty ENT medical residents of Medical Faculty of Sriwijaya University were enrolled as study population. Burnout was measured by Copenhagen Burnout Inventory (CBI) and divided by three parameters (personal,work-related, patient-related). Results. Among 30 ENT resident doctors at Rumah Sakit Moh. Hoesin, the mean level of personal burnout was 53.056 (SD 17.125), work-related burnout was 47.975 (SD 17.663), and patient-related burnout was 34.861 (SD 20.746). Conclusion. Marriage, female gender, and inadequacy of PPE may contribute to the development of burnout. The burnout among resident doctors is a serious matter regarding their role as a frontline doctor during the pandemic era, because it may affect not only their performance at work, but toward their life as well.